2021
DOI: 10.3390/cancers13246279
|View full text |Cite
|
Sign up to set email alerts
|

RNA Biomarkers as a Response Measure for Survival in Patients with Metastatic Castration-Resistant Prostate Cancer

Abstract: Treatment evaluation in metastatic castration-resistant prostate cancer is challenging. There is an urgent need for biomarkers to discriminate short-term survivors from long-term survivors, shortly after treatment initiation. Thereto, the added value of early RNA biomarkers on predicting progression-free survival (PFS) and overall survival (OS) were explored. The RNA biomarkers: KLK3 mRNA, miR-375, miR-3687, and NAALADL2-AS2 were measured in 93 patients with mCRPC, before and 1 month after start of first-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This hypothesis is supported by two of our recent publications. Here we found high plasma-AS2 levels in CRPC patients treated with ARSIs to be favorable for progression free survival and overall survival, while low AS2 levels were unfavorable [39,40]. These findings support the clinical utility of AS2 as a liquid biopsy-based biomarker in CRPC.…”
Section: Discussionsupporting
confidence: 79%
“…This hypothesis is supported by two of our recent publications. Here we found high plasma-AS2 levels in CRPC patients treated with ARSIs to be favorable for progression free survival and overall survival, while low AS2 levels were unfavorable [39,40]. These findings support the clinical utility of AS2 as a liquid biopsy-based biomarker in CRPC.…”
Section: Discussionsupporting
confidence: 79%
“…At present, the established prognostic factors (ISUP, stage, and PSA) are insufficient to separate PC patients with high risk of cancer progression; moreover, molecular markers for metastatic propensity remain elusive [25]. RNA biomarkers are experiencing an increased interest in predicting progression-free survival and OS [26]. In the present article, we reinforced the role of PCA3, MRC2, and S100A4 in combination, and S100A4 on its own, as RNA biomarkers in PC aggressiveness stratification.…”
Section: Discussionmentioning
confidence: 64%
“…Studies also revealed significant upregulation of LncRNA NAALADL2-AS2 in metastatic castration-resistant prostate cancer (mCRPC) and demonstrated NAALADL2-AS2 as a biomarkers of response measure for survival in patients with mCRPC [45]. Androgen regulated lncRNA NAALADL2-AS2 promoted the survival of prostate cancer cells, and transcriptome and pathway analyses revealed that NAALADL2-AS2 modulated the expression of genes involved with cell cycle control and glycogen metabolism [46].…”
Section: Discussionmentioning
confidence: 99%